Navigating IT governance for resilient organizations - Maleh, Yassine 1987-; Sahid, Abdelkebir (Advances in IT standards and standardization research (AITSSR) book series, 2024)
In the world of IT governance, the integration of cybersecurity with organizational agility emerges as critical to organizations facing modern digital adaptation. Cyber-agility advocates for adaptive governance frameworks and agile cybersecurity practices. Emerging technology warrants thorough research into cybersecurity, cloud technology, and internet technology management to discover effective strategies for seamless business integration.Navigating IT Governance for Resilient Organizations systematically explores essential IT governance concepts, methodologies, and strategies. The subject matter centers on IT governance, resilience, and agility, which are pivotal for the success and sustainability of modern organizations. By examining foundational principles, strategic frameworks, and practical implementations, this book provides computer engineers, IT professionals, policymakers, organizational leaders, researchers, academicians, and scientists with the knowledge necessary to ensure robust, adaptable, and secure IT systems.